MEMBELI PERHIASAN EMAS PADA TOKO EMAS JAYA DI SAMARINDA - Nurdiyana, Siti (EKONOMIA, 2013)
SITI NURDIYANA, 2013, Effect of Marketing Mix Decisions Against Buying Gold Jewelry In Gold Store Jaya In SamarindaÂ The purpose of this study to determine the variables pengruh product, price, place and promotion of the consumer decision to buy gold jewelery on Gold Shops Jaya In Samarinda.Basic theory used pemsaran particular marketing mix management by using tools of analysis used multiple linear regression analysis using the F test and t test. The study population is the city of Samarinda who buy gold jewelry Gold Shop In Samarinda Jaya with a total sample of 30 respondents.Based on the analysis and discussion, conclusions of this study: R value or correlation of 0.774 indicates that the relationship between consumer decision (dependent variable) with the product, price, place and promotion (the independent variable) high. Thus the variable product, price, place and promotion can be used as predictors of consumers' decision to buy gold jewelery on Gold Shop Jaya Samarinda.The coefficient of determination (R2) indicates the value of 0.599. This figure shows that the effect of independent variables consisting of a variable product, price, place and promotion together on the dependent variable consumer's decision to buy gold jewelery on Gold Shop Jaya Samarinda by 59.9% and the remaining 49.1% are influenced by variables others are not included in this study F count was 9,337 with an error rate of 0.000> F table 3.37. These results indicate that the independent variables consisting of a variable product, price, place and promotion are jointly significant effect on the dependent variable on consumer decisions gold jewelry Gold Shop Jaya Samarinda. Thus the hypothesis that suspected product, price, place and promotion significantly influence consumers' decision to buy gold jewelery on Gold Shop Jaya Samarinda, received Regression coefficient is positive, it means the whole case to variable quality improvement of products, price, place and promotion, it will increase the consumer's decision to buy gold jewelery on Gold Jewelry Store Jaya in SamarindaVariable product has dominant influence, this is evidenced by the variable t value of 3.631 products is greater than t other variables and the standardized beta coefficient 0.466 is greater than the other variables. This means that the second hypothesis received